Análisis de las condiciones laborales desde el nivel de satisfacción laboral en el sector telecomunicaciones - Henry Orlando Luna Pereira; Luisa Stella Paz Montes; José Orlando García Mendoza (Mundo Fesc)
Business development refers to an organization's ability to create value for society. Employee compensation is a form of compensation through a salary or wage. This contextualization allows us to understand the social phenomenon in the actions of individuals and reason about the potential causes of high turnover. The purpose of this research is to analyze the working conditions offered to employees within the company, identifying the factors that influence job satisfaction. The research is based on a descriptive methodology. The study population is the 1,935 employees employed by the company as of September 2022. The sample consists of 321 employees, based on a simple random probability sample. Sociodemographic characteristics and the level of satisfaction with internal and external factors are systematized. The organizational distribution within the company is acceptable, with 65% operations, 17% administrative, and 8% corporate. Most of the factors analyzed are acceptable, but goals, workloads, training, and coaching are unacceptable (76%). Communication channels with the boss are unsatisfactory (67%). Recognition has a 50% satisfaction rate and requires strengthening recognition and bonus strategies to mitigate the effects of salary levels. External factors have both positive and negative trends in job satisfaction. Negative factors are working conditions, achievements, and responsibility (35%) and are related to assertive leadership. Positive factors are achievements, responsibility, and compensation (44%).